Inteligência artificial e seu impacto no desenvolvimento do pensamento crítico - Sayad, Alexandre Le Voci (2022)
Artificial intelligence (ai) is a multidisciplinary field of knowledge that may seem invisible to human perception, but its consequences are not. its technical advances are already impacting life in society at an unprecedented speed - which is why it now occupies a relevant role in the debate on public policies around the world. the everyday application of deep learning, a technique of the ai machine learning, walks a fine line between practicality and benefits for users, such as how predictive decision-making, and its ethical impacts, related to privacy, bias in results, propagation of prejudices, opacity of the algorithm's operation, among others. as a new mediation (kaufman, 2020), ai systems mediate socialization and communication between human beings and the world around them. in this sense, this research aims to evaluate the impact of artificial intelligence on the formation of so-called critical thinking. this, in turn, has its conceptual limits extended in the universe of public and private education, being used many times as a marketing concept. therefore, in search of accuracy, the research revisits the epistemology of critical thinking from selected essays by theodor adorno and max horkheimer (1989), and the scholars who followed them such as john mcpeck (1981), in addition to, later, evidencing its entry as a pillar of the democratic school by through john dewey (1953). in parallel, the research carried out focuses on the historical review of the birth principles of ai functioning through john mccarthy (2005), kai fu-lee (2019), stuart russell and peter norvig (2009) among others. by analyzing the ethical impacts caused by ai (kaufman, 2019, 2022; villani, 2019; pariser, 2011) in various fields, especially in education (fadel et al., 2020), the research presents how ai actually transforms what we know as critical thinking in five chosen aspects, from its epistemology in comparison to others such as the neomaterialists (lemos, 2016, 2020; kaufman, 2020), to elements that make up its basic principles, such as intellectual autonomy and citizenship